Loneliness from the perspective of children in the city of Posadas, Misiones - Chemisquy, Sonia Noemí (2024)
Loneliness is an affective state characterized by a subjective experience that is accompanied by a negative evaluation of social networks, in terms of the quantity and quality of social ties. In the Argentinean scientific literature, this issue is usually approached from a quantitative point of view, and no studies were found that sought to understand the subjective aspects of this experience in children. Therefore, this study aims to describe loneliness from the perspective of children aged 8 to 12 in the city of Posadas and to analyze childhood loneliness from the the multidimensional model of Hymel et al. (1999) to assess its suitability. A qualitative and descriptive study was carried out. The sample consisted of 34 children aged between 8 and 12 years. With the consent of the children’s parents, semi-structured interviews consisting of four questions about loneliness were conducted, recorded and then transcribed. The categories proposed by the original authors of the model were used to score the responses. The results allowed us to characterize loneliness from the perspective of the participants and showed that the multidimensional model is suitable for assessing loneliness in the city of Posadas, with certain categories standing out: emotional concepts, companionship, and temporary absence, belonging to the affective, cognitive and cognitive dimensions.